Cigarette Smoking Increases the Effect of *Arg/*Arg Genotype of P53 Codon 72 on the Susceptibility to Type 2 Diabetes in Overweight Subjects - Anna Neri; Fulvia Gloria-Bottini; Maria Banci; Andrea Magrini; Egidio Bottini (Journal of Tobacco Stimulated Diseases - Peertechz Publications, 2017)
Background: To study possible interaction between P53 codon 72 and cigarette smoking concerning their effects on the predisposition to T2D in overweight subjects. Methods: We have reexamined the data on 281 subjects admitted to the Hospital for Cardiovascular disease. The subjects gave informed consent to participate in the study that was approved by the Council of Department. P53 codon 72 genotype was determined by DNA analysis. Three way contingency table analysis was performed by a log linear model. Results: We have previously observed that *Pro/*Pro genotype of P53 codon 72 protects overweight subjects from diabetes. P53 codon 72 and cigarette smoking cooperate in the predisposition to T2D of overweight subjects. In smoking subjects carrying the *Arg/*Arg genotype the odds ratio is 15.15 vs 1.31 in carriers of *Pro allele. In non-smoking subjects the odds ratio is 6.70 in carriers of *Arg/*Arg genotype vs 2.70 in carriers of *Pro allele. Conclusions: Our observation suggests that overweight subjects with *Arg/*Arg genotype and smoking habit may have a high risk to become diabetic.